Pengaruh Kepemimpinan dan Sistem Penghargaan terhadap Kinerja Pegawai dengan Kepuasan Kerja sebagai Variabel Media - Nancy Florida Siagian; Ambo Enre; R. Elfrida Panjaitan (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2021)
The purpose of this study was to determine the effect of leadership and reward systems on Employee Performance with job satisfaction as a mediating variable. With a sample of 70 respondents. The tool used is a questionnaire. The results of this study are that leadership has a positive and significant effect on employee performance. The reward system has significant and significant effect on employee performance, leadership and reward systems have a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on employee performance, and leadership, reward systems and job satisfaction has a positive and significant effect on employee performance. With the value of t calculated for leadership variable 2,278 and reward system 3,117 while for job satisfaction as mediation has a value of t count equal to there is a value of 1,994 which means that the value of t count has ‘Sig’ <0,05. R Square of 0.433, means that variations in employee performance can be explained by variations in leadership, reward systems and job satisfaction by 43.3% and the rest explained by other variations not examined